The NRA and Social Media: Power, Multilevel Identity Construction, and Resisting Context Collapse - Gilpin, Dawn R. (AoIR Selected Papers of Internet Research, 2013)
Current scholarship treats organizational and issue identity as a fluid, discursively constructed concept, inextricably bound to the negotiation and maintenance of power structures. The interactive nature of identity construction emphasizes the importance of communicative interactions between stakeholders and organizations in shaping identities. Little exploration has been done to link efforts by organizations to construct their own socially mediated identity and those influencing the identities of issues and publics. This paper uses social and semantic network plus qualitative analysis to investigate the social media strategies adopted by the National Rifle Association (NRA). The NRA constitutes its identities and power through a complex network of relationships, and seeks to personalize the issue to constituent groups through differentiated use of digital media. The analysis conducted offers insights into the ways in which complex organizations may structure their social media presence to construct their identity and influence aggregation patterns among stakeholders.